Ensino de geriatria e gerontologia na área da saúde : formação dos profissionais que atuam no atendimento do idoso na rede de serviços - Lima, Ana Paula Monteiro Fialho (2010)
This study aimed to highlight the disciplines of the courses of Medicine, Nursing, Dentistry, Social Service, Physical Education and Psychology at the Federal University of Sergipe, which programs present subjects related to aging. It also identifies if during these courses the senior was focused as a biopsychosocial being, if these professionals felt the need for training in their area after higher education, if there was training and where it was performed. In this research, a qualitative and quantitative methodology was employed, characterized as a cross-sectional study, exploratory, descriptive and documentary. The following instruments were used: self-applied questionnaire with objective and subjective questions, and spreadsheet for analysis of the disciplines programs. In the qualitative analysis, it was used categorical analysis, and found subcategories were presented. In the quantitative analysis was calculated the frequency of appearance of the subcategories in the responses. For analyze the needs of the elderly, it was used the theory of hierarchy of human basic needs described by Maslow. The research was conducted at the Federal University of Sergipe UFS, hospitals and Basic Health Units UBS of the city of Aracaju-SE. Participated in this survey 265 graduated professionals by UFS and that serve the elderly, and of these, 91 were doctors, 71 nurses, 47 dentists, 32 social workers, 14 physical educators and 12 psychologists. It was obtained as a result that the training of health professional participants did not contribute significantly to the performance of these with the elderly population, according to their responses. It was observed that although formations are still focused on the treatment and prevention of diseases, except in the Social Service course that is more focused on the safety of the elderly, the elderly people needs on being esteemed and loved were seen by these professionals during their academic backgrounds. As additional results of this study were, it was obtained suggestions for improvement of the training, it were been shown that teamwork has hardly existed and that the failure in the education of professionals was reflected in difficulties in the practice of care for the elderly, except the psychologists who, despite having reported failures in their training, connected their difficulties to the physical limitations of the elderly. It was also observed that, despite the need for training of most of professionals, the few were trained and the most of the conducted trainings was organized by the Health Department of the Municipality of Aracaju, only for professionals working in their own UBS. .